Pomegranate peel as a promising source of pectic polysaccharides: A multi-methodological analytical investigation. (15th December 2022) - Balli, Diletta; Khatib, Mohamad; Cecchi, Lorenzo; Adessi, Alessandra; Melgarejo, Pablo; Nunes, Cláudia; Coimbra, Manuel A.; Mulinacci, Nadia
Highlights: Three polysaccharide fractions were obtained from 2 pomegranate variety by decoction. DLS allowed discriminating polysaccharides with similar hydrodynamic volumes. Pectic fractions had diverse acylation and methylation degree after 1 H NMR analysis. Uronic acids analysis confirmed the presence of pectic polysaccharides in peel. Methylation analysis evidenced diverse polysaccharide structures in diverse varieties. Abstract: Polysaccharides from pomegranate peel (Wonderful and Purple Queen® varieties) were extracted by hot water and fractionated using ethanol. Three fractions (F1-F2-F3) were obtained for each sample. Polysaccharides' yield was higher for Purple Queen®: 13% dw. Polysaccharides of the three fractions were characterized by size exclusion chromatography ( SEC ), dynamic light scattering (DLS), 1 H NMR, methylation, and acylation degree. Differently from SEC, DLS highlighted some differences between the polysaccharides's molecular sizes of the fractions. The highest methylation and acylation degree was observed for F3 of Purple Queen®: 74.0% and 18.6%, respectively. The percentage of galacturonic acid confirmed the presence of pectin in almost all the fractions recognized as homogalacturonan. Arabinan and arabinogalactan were also found in all the collected F3 samples, although in different proportions. The stepwise fractionation process followed by a multi-methodological analytical investigation was helpful to improve the knowledge of the pectic polysaccharides of pomegranate.